Variation of inversion delay for wrist joint MR imaging with SPAIR technique: which ID is optimal? - Susanto, Fani; Utami, Hernastiti Sedya (Universitas Muhammadiyah Purwokerto, 2021)
Background: The current fat suppression technique in magnetic resonance imaging (MRI) significantly diagnoses abnormalities in musculoskeletal disorders. The spectral attenuated inversion recovery (SPAIR) fat suppression (FS) technique had an inversion delay (ID) parameter that allows choosing between full or partial FS. This was the first research related to the optimal setting of the ID time variation in the SPAIR technique on T2-weighted MRI wrist joint images.Objectives: This study aims to find out anatomical information with the most optimal ID value of the MRI wrist joint image T2 turbo spin-echo (TSE) FS SPAIR coronal slice sequence.Method: This study was a pre-experimental post-test only. Scanning MR wrist joint 16 volunteers took data with the qualitative analysis used three radiologists (visual grading) with statistical data analysis.Results: Image information of the MRI wrist joint T2 TSE FS SPAIR coronal slices sequence showed differences in the variation of ID (p<0.001), where the ID of 85 ms produced the most optimal image information.Conclusion: MRI image of the wrist joint of the T2 TSE FS SPAIR coronal slices sequence the most optimal with an ID variation of 85 ms compared to ID 70 ms and 100 ms.